Fluid Dynamics in Microchannels - Teng, Jyh-tong; Chu, Jiann-Cherng; Liu, Chao; Xu, Tingting; Lien, Yih-Fu; Cheng, Jin-Hung; Huang, Suyi; Jin, Shiping; Dang, Thanhtrung; Zhang, Chunping; Yu, Xiangfei; Lee, Ming-Tsang; et al. (IntechOpen, 2012)
None